Security hardening of pharmacy information system against machine learning attack / Mohd Ghazali Ismail - Ismail, Mohd Ghazali (Faculty of Pharmacy, 2023)
A pharmacy information system (PIS) is a specialised software application designed to support and manage the operations of a pharmacy or a pharmacy department within a healthcare organisation. It is a comprehensive solution that automates various tasks and processes involved in pharmacy management, including medication dispensing, inventory management, patient data management, billing and invoicing, and other administrative functions. The PIS streamlines pharmacy workflows, reduces medication errors, improves efficiency, and enhances patient safety. They play a vital role in supporting the day-to-day operations of pharmacies, ensuring accurate dispensing of medications, and maintaining proper medication management practises. When it comes to securing a PIS against machine learning attacks, there are several steps that the users can take to enhance its security. Machine learning attacks typically involve exploiting vulnerabilities in the system to manipulate or compromise the machine learning models.